Tropomyosin Flexural Rigidity and Single Ca2+ Regulatory Unit Dynamics: Implications for Cooperative Regulation of Cardiac Muscle Contraction and Cardiomyocyte Hypertrophy - Loong, Campion K.; Badr, Myriam A.; Chase, P. B. (Frontiers in Physiology, 2012)
Striated muscle contraction is regulated by dynamic and cooperative interactions among Ca2+, troponin, and tropomyosin on the thin filament. While Ca2+ regulation has been extensively studied, little is known about the dynamics of individual regulatory units and structural changes of individual tropomyosin molecules in relation to their mechanical properties, and how these factors are altered by cardiomyopathy mutations in the Ca2+ regulatory proteins. In this hypothesis paper, we explore how various experimental and analytical approaches could broaden our understanding of the cooperative regulation of cardiac contraction in health and disease.